Comparison of 2 Disability Measures, Behavioral Risk Factor Surveillance System, 2013 - Stevens, Alissa C. (Prev Chronic Dis, 2016)
INTRODUCTION: Beginning in 2013, in addition to the 2-item disability question set asked since 2001, Behavioral Risk Factor Surveillance System (BRFSS) began using 5 of the 6 items from the US Department of Health and Human Services–recommended disability question set. We assess and compare disability prevalence using the 2-question and 5-question sets and describe characteristics of respondents who identified as having a disability using each question set. METHODS: We used data from the 2013 BRFSS to estimate the prevalence of disability for each question set and the 5 specific types of disability. Among respondents identified by each disability question set, we calculated the prevalence of selected demographic characteristics, health conditions, health behaviors, and health status. RESULTS: With the 2-question set, 21.6% of adults had a disability and with the 5-question set, 22.7% of adults had disability. A total of 51.2% of adults who identified as having a disability with either the 2-question or 5-question set reported having disabilities with both sets. Adults with different disability types differed by demographic and health characteristics. CONCLUSION: The inclusion of the 5 new disability questions in BRFSS provides a level of detail that can help develop targeted interventions and programs and can guide the adaptation of existing health promotion programs to be more inclusive of adults who experience specific types of disabilities.